Technological Intelligence as an Intervening Effect of Knowledge Management and Intellectual Capital for Enhancing Competitive Advantage in Educational Institutions - Jam'iyyatul Khoiriyah; Ali Imron; Sunarni Sunarni (Universitas Negeri Malang, 2025)
The urgency in managing information in today's digital century, the goal of management is to increase the productivity of knowledge workers and knowledge work by using the most valuable resource in the form of intellectual capital in the knowledge management process. This research examines the role of technological intelligence as an intervening variable between the influence of knowledge management and intellectual capital on the competitive advantage of educational institutions using a correlational quantitative research design with a research population of educators and educational staff at Upper Secondary Education (Madrasah Aliyah, Senior High Schools, and Vocational Schools) in Malang City, East Java, Indonesia. Data collection used a simple random sampling technique by questionnaire distribution to 376 respondents in 25 schools. Data analysis uses the SmartPLS4 application by testing correlation and analyzing paths in the form of Partial Least Square Structural Equation Modeling (PLS-SEM). The results show that knowledge management and intellectual capital have a significant positive effect on the competitive advantage of educational institutions. Furthermore, technological intelligence is proven to mediate knowledge management and intellectual capital’s connection to competitive advantage. These findings indicate that the effective use of information and communication technology can strengthen knowledge management and intellectual capital contribution in increasing the competitiveness of educational institutions. The implications of this research highlight the concern of investing in technological intelligence, developing a culture of knowledge sharing, and optimizing intellectual assets to achieve competitive advantage in educational institutions.